Special topics in transport phenomena - Astarita, Giovanni (Elsevier Science, 2002)
This book is a research monograph on transport phenomena. The topics discussed are often mathematically simple, though conceptually complex. The book is written in a colloquial style which a good teacher uses in the classroom. It originates from the author's wealth of teaching experience in this area and incorporates suggestions from colleagues worldwide.